Social skins of the head body beliefs and ritual in ancient Mesoamerica and the Andes - Lozada Cerna, María Cecilia; Tiesler, Vera (Albuquerque University of New Mexico Press, 2018)
"The meanings of ritualized head treatments among ancient Mesoamerican and Andean peoples is the subject of this book, the first overarching coverage of an important subject. Heads are sources of power that protect, impersonate, emulate sacred forces, distinguish, or acquire identity within the native world. The essays in this book examine these themes in a wide array of indigenous head treatments, including facial cosmetics and hair arrangements, permanent cranial vault and facial modifications, dental decorations, posthumous head processing, and head hunting. They offer new insights into native understandings of beauty, power, age, gender, and ethnicity. The contributors are experts from such diverse fields as skeletal biology, archaeology, aesthetics, forensics, taphonomy, and art history."--
Introducing the social skins of the head in ancient Mesoamerica and the Andes / Vera Tiesler and María Cecilia Lozada -- What was being sealed? : cranial modification and ritual binding among the Maya / William N. Duncan and Gabrielle Vail -- Head shapes and group identity on the fringes of the Maya lowlands / Vera Tiesler and Alfonso Lacadena -- Head shaping and tooth modification among the classic Maya of the Usumacinta River kingdoms / Andrew K. Scherer -- Cultural modification of the head : the case of Teopancazco in Teotihuacan / Luis Adrián Alvarado-Viñas and Linda R. Manzanilla -- Face painting among the classic Maya elites : an iconographic study / María Luisa Vázquez de Ágredos Pascual, Cristina Vidal Lorenzo, and Patricia Horcajada Campos -- The importance of visage, facial treatment, and idiosyncratic traits in Maya royal portraiture during the reign of K'inich Janaab' Pakal of Palenque, 615-683 CE / Laura Filloy Nadal -- The representation of hair in the art of Chichén Itzá / Virginia E. Miller -- Effigies of death : representation, use, and reuse of human skulls at the Templo Mayor of Tenochtitlan / Ximena Chávez Balderas -- Emic perspectives on cultural practices pertaining to the head in Mesoamerica : a commentary and discussion of the chapters in part one / Gabrielle Vail -- Afterlives of the decapitated in ancient Peru / John W. Verano -- Head processing among La Ramada tradition of Southern Peru / María Cecilia Lozada, Alanna Warner-Smith, Rex C. Haydon, Hans Barnard, Augusto Cardona Rosas, and Raphael Greenberg -- From Wawa to "Trophy Head" : meaning, representation, and bioarchaeology of human heads from ancient Tiwanaku / Deborah E. Blom and Nicole C. Couture -- Cranial modification in the central Andes : person, language, political economy / Bruce Mannheim, Allison R. Davis, and Matthew C. Velasco -- Violence, power, and head extraction in the Kallawaya Region, Bolivia / Sara K. Becker and Sonia Alconini -- Semiotic portraits : expressions of communal identity in Wari faceneck vessels / Andrea Vazquez de Arthur -- Using their heads : the lives of crania in the Andes / Christine A. Hastorf.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Indians -- Craniology; Indians -- Anthropometry; Head ; Mythology; Head ; Religious aspects; Indians of Central America ; Antiquities; Indians of Central America ; Material culture; Indians of Central America ; Social life and customs; Indians of Mexico ; Antiquities; Indians of Mexico ; Material culture; Indians of Mexico ; Social life and customs; HISTORY ; Latin America ; Mexico; History; HEAD in art